1992
DOI: 10.1021/jm00090a021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of analogs of (Z)-1-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)ethene as potential cytotoxic and antimitotic agents

Abstract: A series of stilbenes has been prepared and tested for cytotoxicity in the five human cancer cell lines A-549 non-small cell lung, MCF-7 breast, HT-29 colon, SKMEL-5 melanoma, and MLM melanoma. The cis stilbenes 6a-f proved to be cytotoxic in all five cell lines, with potencies comparable to that of combretastatin A-4. These cytotoxic compounds were all potent inhibitors of tubulin polymerization. The corresponding trans stilbenes 7b-f were inactive as tubulin polymerization inhibitors and were significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
188
1
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(213 citation statements)
references
References 5 publications
21
188
1
3
Order By: Relevance
“…Why only these two agents (4b,7b) cause this block is not known, particularly as no disruption of the intracellular microtubular network was observed even at 50 gIM. In general, these studies are in agreement with the report by Cushman et al (1992) that the cis-methyl and -ethyl derivatives (3a,4a) inhibit tubulin assembly. This present study further characterises the interaction of agents of this type with tubulin.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Why only these two agents (4b,7b) cause this block is not known, particularly as no disruption of the intracellular microtubular network was observed even at 50 gIM. In general, these studies are in agreement with the report by Cushman et al (1992) that the cis-methyl and -ethyl derivatives (3a,4a) inhibit tubulin assembly. This present study further characterises the interaction of agents of this type with tubulin.…”
Section: Discussionsupporting
confidence: 92%
“…(d) The 3'-hydroxyl group has a relatively small effect on binding to tubulin (Cushman et al, 1992). (e) The 4'-methoxy group of combretastatin A-4 (1) can be replaced with small hydrophobic groups while still retaining significant activity against tubulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAR studies of CA-4 have underlined that the presence of a 3,4,5-trimethoxy-substituted A-ring and 4-methoxy-substituted B-ring separated by a double bond with the cis-configuration are fundamental for anti-proliferative activity [3]. It has also been reported that the 3-hydroxy group on the B-ring is not necessarily determinant for potent activity [63,64]. Cushman et al [64] synthesized a series of 4'-methoxy-3,4,5-trimethoxy-cis-stilbene derivatives where the methoxy group in the B-ring was replaced with a variety of other substituents.…”
Section: Other Synthetic Stilbene Derivatives As Tubulin-interactive mentioning
confidence: 99%
“…It has also been reported that the 3-hydroxy group on the B-ring is not necessarily determinant for potent activity [63,64]. Cushman et al [64] synthesized a series of 4'-methoxy-3,4,5-trimethoxy-cis-stilbene derivatives where the methoxy group in the B-ring was replaced with a variety of other substituents. The most potent tubulin polymerization inhibitor, 4'-methoxy-3,4,5-trimethoxy-cisstilbene, influenced tubulin assembly with an IC 50 of 2.0 M comparable to CA-4.…”
Section: Other Synthetic Stilbene Derivatives As Tubulin-interactive mentioning
confidence: 99%